LEGALITAS TAX PLANNING ATAS PAJAK PENGHASILAN - Kara Mustafa (Aliansi : Jurnal Manajemen dan Bisnis, 2018)
This study aims to analyze the Legality of Tax Planning on Income Tax. The method used in the writing of this research is the method of writing normative law, namely the way of writing based on the analysis of some legal principles and legal theory and legislation appropriate and related to the problems in this study. Tax Planning Legality on Income Tax is a general tax planning refers to the process of business engineering and taxpayer transactions Agency so that tax debt is in the minimal amount, but still within the frame of the regulation. With Tax Planning Legality on Income Tax is expected to perform the tax obligations and tax control can be done as well as possible. Collection and research on regulations are conducted to prove that tax planning can be done legally.